Metals in herbal formulations - Helal Uddin, A.B.M. (IIUM Press, 2011)
Traditional medicine has historical, cultural, religious and social bases. It has been accepted and endorsed as a means of health complications from ancient time. The approach and application could have differences based on different types of traditional medicines but one thing is common is that it carries the cultural social identity of the civilization. As the time passes and urbanization and mordenisation is excelling for last few decades it \"'as expected that the dependency will become more on modern conventional therapy. But surprisingly the trend 0 consumption of traditional medicine has gained popularity and getting attention from the users ofthe countries advocating modern medicine. Due to the growing popularity WHO has to come out \vith guidelines and policies for the approval of TM at a wider aspect. Lack of formal research, systematic development of protocols, standard analysis methods make the TM questionable from the safety and efficacy point of view. It is very important to conduct proper research study ofTM to ensure the safety and efficacy of the TM.